Viscoelastic Damping Devices Proving Effective in Tall Buildings - Caldwell, D.B. (Engineering Journal, 1986)
When the World Trade Center in New York City opened its doors as the tallest building in the world in 1972, it gained instant public attention. But a design first in the 110-story twin towers was, and still is, little noticed outside the group of engineers and scientists that were close to the project. That design feature is the 20,000 viscoelastic dampers in the structural system that absorb the punch of unusual as well as average winds. The dampers reduce perceived sway and acceleration in the upper floors. They do this job by absorbing and dissipating vibrational energy transmitted by the wind to structural members. Although that application was 14 years ago, viscoelastic vibration damping devices are relatively new in the sense they have presently been used in only two tall buildings. Nevertheless, the devices offer a number of advantages, and for that reason were selected to be incorporated in the second structure, Seattles 76-story Columbia Center. The effect of damping, or the dissipation of energy from a vibrating system, is well known to every structural engineer. When wind meets the face of a tall building, air spins off around the structure in vortices that push the building back and forth, transverse to the direction of the wind. This movement is damped by air resistance, friction at joints and internal friction in the building materials. In almost all cases, engineers rely on methods such as the structural systems, mass and shape of the building, to provide damping effect.